2005
DOI: 10.1159/000088983
|View full text |Cite
|
Sign up to set email alerts
|

Spouses’ Quality of Life 1 Year after Stroke: Prediction at the Start of Clinical Rehabilitation

Abstract: Background and Purpose: The purpose of this prospective study was to identify early predictors of spouses’ quality of life at 1 year after stroke. Methods: At the start of clinical rehabilitation patient and caregiver characteristics, psychological factors, harmony in the relationship and social support were assessed. One year after stroke, caregiver burden (Caregiver Strain Index), life satisfaction (Life Satisfaction Checklist) and depressive symptoms (Goldberg Depression Scale) were assessed in 187 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
117
3
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 52 publications
10
117
3
5
Order By: Relevance
“…13 Inclusion criteria for patients were: first-ever stroke, supratentorial and one-sided lesion, and age Ͼ18 years. Exclusion criteria for patients were disabling comorbidity (prestroke Barthel Index Ͻ18) and inability to speak Dutch.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Inclusion criteria for patients were: first-ever stroke, supratentorial and one-sided lesion, and age Ͼ18 years. Exclusion criteria for patients were disabling comorbidity (prestroke Barthel Index Ͻ18) and inability to speak Dutch.…”
Section: Subjectsmentioning
confidence: 99%
“…In an earlier study, 13 our research group identified "passive coping strategy" as the most important negative predictor of spouses' quality of life 1 year poststroke. Coping styles are related to the psychosocial well-being of persons who are confronted with a negative or stressful life event.…”
mentioning
confidence: 90%
“…22,23 The Dutch LiSat-9 has previously been used and showed satisfactory internal consistency reliability (Cronbach's alpha 0.74-0.85). 24,25 Demographic variables taken into account were age and sex. Disease characteristics taken into account were type of SB (occulta or aperta), the level of the lesion (defined as the lowest completely unimpaired level on both sides with sensitivity to pin prick and light touch), and the presence of HC (defined as having been shunted early in life to reduce intracranial pressure).…”
Section: Instrumentsmentioning
confidence: 99%
“…In fact, other studies have demonstrated that stroke survivor cognitive/memory and emotional problems and functional deficits often lead to both caregiver 2,4 and stroke survivor 22,23 depressive symptoms and to lower caregiver life satisfaction. 5,24 The unique contribution of our findings is the mediational results. Even after controlling for demographic variables, caregiver well-being accounted for substantial amounts of variance in the relationship between stroke survivor impairments and problems and stroke survivor depressive symptoms.…”
Section: Discussionmentioning
confidence: 67%
“…5 Stroke survivor impairments and problems affect many aspects of daily living for caregivers, but data also suggest that caregivers who have a positive well-being, including few depressive feelings 6 and higher life satisfaction, 7 may be better emotionally equipped to handle the stresses of caregiving 5 and potentially reduce stroke survivor depressive symptoms. 8 Although stroke survivor impairments and problems, caregiver depressive symptoms and life satisfaction, and survivor depressive symptoms appear to be related, the direction of these relationships remains unclear.…”
mentioning
confidence: 99%